Briefs short reports on current agricultural research: Fresh-seed dormancy in annual grasses - H Laude (California Agriculture, 1962)
Leaf analysis standards for macroelements of orange trees in California can be expected to differ when 4- to 6-month-old leaves are taken from nonfruiting or fruiting terminals. These conclusions are based on a recent study of 22 representative orange orchards extending from the Mexican border to Ivanhoe, California.